Respostas

2013-10-24T20:08:15-02:00
Resolva as equações 
a ) 2 (x-1)/3  +  x+2/2 = 1  
2x-2 + x+2  =1  mmc=6
   3        2
2( 2x-2) + 3( x+2) =6
4x -4 + 3x +6 =6
4x+3x = 6 - 6 +4
7x=4
x=  4  
       7
  
b ) 2x-5/10  -  1-x/5 = 0 
 2x - 5  -   1 -x       =o   mmc= 10
     10          5
2x-5  - 2 ( 1-x) =0
2x-5 -2 +2x =0
4x= 7
x= 7/4

c ) 2/3 x + 1/4 x = 6  mmc=12
6x + 3x = 72
9x=72
x= 72/9
x=8
2013-10-24T20:10:53-02:00
2)a) 2x-2/3 + x+2/2 = 1
      2 (2x-2)/3 + 3 (x+2)/2 = 1
      (4x-4 + 3x+6)/6 = 1 [cancela o denominador]
       4x+3x+6-4=1
       7x+2=1
       7x=-1
       x= -1/7

b) 2x-5/10 - 1-x/5 =0
    (2x-5 - 2-2x)/10=0 [cancela o denominador]
     2x-2x-5-2=0
     resposta inexistente

c) 2/3 x + 1/4 x = 6
    8x+3x/12= 6 [cancela o denominador]
    8x+3x=6
    11x=6
     x= 6/11

espero que esteja certo e tenha te ajudado